Microsoft Azure AI fundamentals (AI-900) certification course essential knowledge to prepare for and pass the exam - Taulli, Tom (O'Reilly Media, Inc., 2025)
This course offers a deep dive into the AI-900: Microsoft Azure AI Fundamentals exam, helping learners understand key AI concepts such as machine learning, computer vision, and generative AI using Azure's AI tools. Throughout this course, Azure expert Tom Taulli will help you get to know Azure's powerful AI toolkit while showing you how to build practical, real-world skills that employers demand. You'll learn to harness Azure Machine Learning, Cognitive Services, and OpenAI capabilities, walking away with both the theoretical knowledge and hands-on experience needed to implement AI solutions effectively. Plus, you'll get expert guidance on exam preparation, ensuring you're fully equipped to ace the certification and take your career to the next level. Whether you're a tech professional looking to expand your skillset or an organization aiming to drive AI transformation, this certification is your gateway to the future of AI. What you'll learn and how to apply it By the end of this course, the learner should understand the details of the AI-900 exam. By the end of this course, the learner should understand the core concepts of AI, such as the fundamentals of machine learning, cognitive services (including vision, language, and speech processing), and responsible AI principles. By the end of this course, the learner should understand the main Azure AI solutions that are part of the AI-900 exam, from Azure Machine Learning to Azure OpenAI. This course is for you because You're a programmer who wants to expand your skillset with a solid foundation in AI principles and apply machine learning concepts using Microsoft Azure, all without requiring a deep background in data science. You're a professional in a business, sales, or project management role who is looking to transition into technical positions like a data analyst or AI solutions developer. You're an IT professional, cloud architect, or data specialist seeking to advance in your current role by building proficiency in AI and machine learning. Prerequisites Basic understanding of AI and generative AI-such as the differences between them and how machine learning and deep learning work-is helpful knowledge, but not required No prior experience with Azure is required, but a basic understanding of cloud computing concepts is helpful.
Online resource; title from title details screen (O'Reilly, viewed March 17, 2025)
Keywords: Artificial intelligence -- Study guides -- Examinations; Microsoft Azure (Computing platform) -- Study guides -- Examinations; Intelligence artificielle; Examens; Guides de l'étudiant; Microsoft Azure (Plateforme informatique); Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet